2016
DOI: 10.1002/adfm.201600713
|View full text |Cite
|
Sign up to set email alerts
|

Design of Strain‐Limiting Substrate Materials for Stretchable and Flexible Electronics

Abstract: Recently developed classes of electronics for biomedical applications exploit substrates that offer low elastic modulus and high stretchability, to allow intimate, mechanically biocompatible integration with soft biological tissues. A challenge is that such substrates do not generally offer protection of the electronics from high peak strains that can occur upon large-scale deformation, thereby creating a potential for device failure. The results presented here establish a simple route to compliant substrates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(79 citation statements)
references
References 30 publications
1
78
0
Order By: Relevance
“…It can be observed that array of microwavy structure is formed on the surface of Cu film electrode during the dry transfer process, which can effectively overcome the fundamental mismatch in mechanics between the different materials. [39] Simulation analysis and experimental investigations reported by Huang and coworkers [40] have also confirmed that the novel wavy structure can not only flex but also stretch and compress, with a mechanics similar to that of accordion bellows (Figure 10c). Hence, the formation of this special peculiar structure can successfully avoid fracture and electrical failure of the conductive metal film when bending to some extent, thus improving the fatigue-free performance.…”
Section: Reliability Of the Cu Film Electrodesupporting
confidence: 53%
“…It can be observed that array of microwavy structure is formed on the surface of Cu film electrode during the dry transfer process, which can effectively overcome the fundamental mismatch in mechanics between the different materials. [39] Simulation analysis and experimental investigations reported by Huang and coworkers [40] have also confirmed that the novel wavy structure can not only flex but also stretch and compress, with a mechanics similar to that of accordion bellows (Figure 10c). Hence, the formation of this special peculiar structure can successfully avoid fracture and electrical failure of the conductive metal film when bending to some extent, thus improving the fatigue-free performance.…”
Section: Reliability Of the Cu Film Electrodesupporting
confidence: 53%
“…Three-dimensional finite element analysis using a software (ABAQUS, Dassault Systems, Waltham, MA) was conducted to investigate mechanical behaviors of an electrode upon skin deformations: bending and stretching (Chen et al 2016; Ma et al 2016). The soft electrode used in EOG measurement was composed of three layers including 300 nm-thick Au, 1 µm-thick polyimide (PI; HD MicroSystems, Parlin, NJ), and 5 µm-thick silicone elastomer (Smooth-On, Macungie, PA; details in Supplementary Figure S1).…”
Section: Methodsmentioning
confidence: 99%
“…Comparison of the potential energy in equations (2.2) and (2.10) suggests that wrinkling occurs when U bend > U bend+wrinkle , which gives [22], which neglects the effect of film/substrate bending. Figure 3 shows the critical pre-strain ε c pre versus the thickness ratio H/h for a polyimide film (E f = 2.5 GPa, v f = 0.34) on a polydimethylsiloxane substrate (E s = 1 MPa, v s = 0.5).…”
Section: -3mentioning
confidence: 99%
“…The recent study by Ma et al [22] accounted for (1), while this paper aims to establish an analytic model for both (1) and (2). The resulting critical pre-strain will be useful for many applications such as the strain-limiting design of materials [22] and tuneable optical design of the intensity for diffraction peaks [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation